(untitled) (Communication & Society, 2008)
Interactive television, also referred to as ITV, has already covered a long distance but has not reached massive deployment yet.This article analyses the criteria that ITV producers are currently following in order to ensure that their work meets the expectations of viewers and that it gets its most out the capabilities of the medium. First, we identify some key issues of ITV production, related to content selection, audience research, use of interactivity and business models. Then, we survey the criteria followed by producers in the above mentioned aspects of ITV production. The results are discussed. The emphasis is placed on the producers’ perceptions as indicators of the level of maturity of the industry, considering content, audience knowledge, use of interactivity and the business models that the new technological and market developments imply. Results suggest that ITV is in an advanced stage in which producers are ready to leave some of the positions of the past, which may help its massive deployment.